Literature review of Notch melanoma receptors - Renato Santos de Oliveira Filho; Alexandre Lavorato Soares; Francisco Macedo Paschoal; Gisele Gargantini Rezze; Ebe Oliveira; Ricardo Macarenco; Antonio Carlos Buzaid; Lydia Masako Ferreira (BMC, 2019)
Abstract Despite the immunotherapeutics and target therapy agents, the survival of patients with advanced melanoma is still low. Notch signaling is able to regulate many aspects of melanomagenesis. Comparative analyses of common melanocytic nevi, dysplastic nevi and melanomas demonstrated increased expression of Notch1, Notch2 and their ligands, indicating that a positive regulation of these components may be related to the progression of melanoma. Some strategies such as gamma-secretase inhibitors (GSI) have been explored in patients with refractory metastatic disease or locally advanced disease of solid tumors. Two major classes of Notch inhibitors are currently in clinical development: GSI and monoclonal antibodies against Notch receptors or their ligands. Inhibition of Notch by GSI has been shown to decrease melanoma growth. GSI RO4929097 co-administered with cisplatin, vinblastine and temozolomide promotes greater elimination of tumor cells. The Notch pathway needs to be explored in the treatment of melanoma.